Cardiopulmonary response to high‐altitude mountaineering in lung transplant recipients—The Jebel Toubkal experience. (26th July 2021) - Schrutka, Lore; Slama, Alexis; Muehlbacher, Jakob; Bessa, Vasiliki; Lichtenegger, Paul; Ghimessy, Áron; Ebenbichler, Gerold; Winkler, Roland; Faybik, Peter; Nachbaur, Edith; Aigner, Clemens; Hoetzenecker, Konrad; et al.
Abstract : Objectives: Only a small proportion of lung transplant recipients achieve a physical status comparable to healthy individuals in the long term. It is reasonable to hypothesize that the necessary cardiopulmonary adaptation required for strenuous physical exercise may be impaired. Exposure to high altitude provides an optimal platform to study the physiological cardiopulmonary adaptation in lung transplant recipients under aerobic conditions. To gain a deeper understanding, 14 healthy lung transplant recipients and healthcare professionals climbed the highest peak in North Africa (Mount Jebel Toubkal; 4167 m) in September 2019. Methods: Monitoring included daily assessment of vital signs, repeated transthoracic echocardiography, pulmonary function tests, and capillary blood sampling throughout the expedition. Results: Eleven out of fourteen lung transplant recipients reached the summit. All recipients showed a stable lung function and vital parameters and physiological adaptation of blood gases. Similar results were found in healthy controls. Lung transplant recipients showed worse results in the 6‐minute walk test at low and high altitude compared to controls (day 1: 662 m vs. 725 m, p  < 0.001, day 5: 656 m vs. 700 m, p  = 0.033) and a lack of contractile adaptation of right ventricular function with increasing altitude as measured by tricuspid plane systolic excursion on echocardiography (day 2: 22 mm vs. 24 mm, p  = 0.202, day 5: 23 mm vs. 26 mm, p  = 0.035). Conclusions: Strenuous exercise in healthy lung transplant recipients is safe. However, the poorer cardiopulmonary performance in the 6‐minute walk test and the lack of right ventricular cardiac adaptation may indicate underlying autonomic dysregulation.